ANALYSIS OF FINANCIAL PERFORMANCE WITH USING ECONOMIC VALUE ADDED: A STUDY ON INDOFOOD CBP SUKSES MAKMUR - Yanti; Isyanto, Puji; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the financial performance. Indofood CBP Sukses Makmur Tbk in 2015 until 2018, based on the method of EVA. The data used in this study a financial statement data from 2015 to 2018 year. Data analysis method used is descriptive statistical analysis methods. From the data analysis berdasarkankan EVA method shows good performance for over 4 years of research EVA company shows a negative value ((EVA